Electronic, elastic, optical and thermal transport properties of penta-PdAs2 monolayer: First-principles study. (February 2020) - Pan, Xiao-Long; Zhao, Ying-Qin; Zeng, Zhao-Yi; Chen, Xiang-Rong; Chen, Qi-Feng
Abstract: PdAs2 monolayer, a new pentagonal two-dimensional (2D) material, greatly attracts widely research interest due to its extremely high carrier mobility with a direct band gap. We have systematically studied the electronic structure, elastic, optical and thermal transport properties of monolayer PdAs2 from first-principles calculations. Our electronic structure calculations show that the monolayer PdAs2 is a semiconductor with a direct band gap of 0.78 eV. Tensile strain has a good regulating effect on the band gap, which can be adjusted from 0.01 eV to 0.84 eV. The calculated elastic constants of monolayer PdAs2 confirm that the PdAs2 monolayer is mechanically stable. The calculated optical properties reveal that the energy range of the absorption spectrum is 1 eV–15 eV. The absorption range of PdAs2 monolayer is mainly visible and ultraviolet light. Under the tensile strain, the absorption spectrum shows obvious redshift. With the increase of strain, the reflectivity and refractivity increase. The calculated thermal conductivity of the monolayer PdAs2 at 300 K is 1.04 W/(mK), which is lower than that of known pentagonal monolayer. In addition, the effects of phonon free path, group velocity and phonon scattering rate on lattice thermal conductivity are analyzed. Highlights: PdAs2 monolayer is shown to be dynamically and mechanical stable. PdAs2 monolayer has a tunable band gap under tensile strain. The optical properties of PdAs2 monolayer under tensile strain are discussed. PdAs2 monolayer is first investigated to be low thermal conductivity pentagonal material